2018
DOI: 10.1177/2050640617717157
|View full text |Cite
|
Sign up to set email alerts
|

Educational strategies for colonoscopy bowel prep overcome barriers against split‐dosing: A randomized controlled trial

Abstract: Background: A split-dose (SD) regimen is crucial for colonoscopy quality. Compliance with SD for early morning colonoscopy is generally poor. The present study evaluated whether pre-colonoscopy counselling, in addition to a dedicated leaflet, might increase SD uptake. Methods: Consecutive 50-69-year-old patients undergoing screening colonoscopy before 10 a.m. were randomized to either receive written information only on bowel preparation (Written Group, WG) or written and oral instructions (Written and Oral Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In this sense, the rationale of education seems extremely valuable for mobilized patients, who perhaps should be the principal target for healthcare practices. A recent RCT showed that mobilized outpatients receiving written or written and oral instructions achieved high rates of compliance with the preparation schema (split-dose) and consequently adequate bowel cleansing 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the rationale of education seems extremely valuable for mobilized patients, who perhaps should be the principal target for healthcare practices. A recent RCT showed that mobilized outpatients receiving written or written and oral instructions achieved high rates of compliance with the preparation schema (split-dose) and consequently adequate bowel cleansing 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that 10-min conversations surrounding preparation details given along with written instructions significantly improve the quality of BP when compared to the absence of counseling sessions [ 10 , 20 ]. Further studies found that written instruction leaflets were better than verbal BP instructions [ 21 ]. Additional research and intervention are needed to define the best approaches to closing this gap in understanding.…”
Section: Discussionmentioning
confidence: 99%
“…6 The practical consequence is that they may have a suboptimal prep, but better education may help. 7 Head-to-head studies of bowel preps have only recently become available. Gu et al found in a large non-commercial 'real-world' prospective multicenter trial with 4339 colonoscopies and 75 endoscopists that MiraLAX with Gatorade, Movi-Prep and Suprep were associated with superior tolerability and bowel cleansing.…”
Section: Recent Advances In Clinical Practicementioning
confidence: 99%
“… 6 The practical consequence is that they may have a suboptimal prep, but better education may help. 7 …”
Section: Acquisition Stagementioning
confidence: 99%